Z historii badań traseologicznych w polskiej archeologii epoki kamienia - Małecka-Kukawka, Jolanta (Folia Praehistorica Posnaniensia, 2018)
The paper is an outline of history of the tool function studies in the Polish Stone Age archaeology. An experimental-traseological method of the Russian scholar S. A. Semenov has been known in archaeology for about forty years. This microscopic method of tool function identification has soon become one of the most important methods of archaeological data analysis from the oldest phases of prehistory. The paper discusses reasons of a poor reception of traseology in Poland. This lack of reflection on tool function is linked to a dominant culture-historical paradigm in Stone Age archaeology.